1972
DOI: 10.1002/1097-0142(197207)30:1<91::aid-cncr2820300115>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate complications of laryngectomy following high-dose preoperative radiotherapy

Abstract: During the most recently completed academic year (July 1969 to July 1970), 24 laryngectomies were performed for squamous cell carcinoma of the larynx. Twenty‐two of these laryngectomies followed high‐dose preoperative radiotherapy. Of this latter group, 14 represented a planned course of preoperative radiotherapy (5,000 rads in 5 weeks) followed by laryngectomy after a waiting period of 4 to 6 weeks. The remaining eight cases represented the surgical salvage of radiation failures. No mortality or major complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…I n those patients in Group 2 of the present study this was performed according to the following guidelines : I A U-flap (Gluck-Saerensen) was usually employed (Figure 3). 2 Resection of skin for stoma through lower portion of the U-flap (Figure 3). 3 A wide field laryngectomy including hyoid bone and isthmus and lobe of the thyroid gland on the most affected side was always performed-especially in fixed cord cases.…”
Section: Discussionmentioning
confidence: 99%
“…I n those patients in Group 2 of the present study this was performed according to the following guidelines : I A U-flap (Gluck-Saerensen) was usually employed (Figure 3). 2 Resection of skin for stoma through lower portion of the U-flap (Figure 3). 3 A wide field laryngectomy including hyoid bone and isthmus and lobe of the thyroid gland on the most affected side was always performed-especially in fixed cord cases.…”
Section: Discussionmentioning
confidence: 99%
“…(REPRINTED) ARCH OTOLARYNGOL HEAD NECK SURG/ VOL 132, JAN 2006 hemoglobin level and preoperative radiotherapy represent significant RRs in the pooled analysis, there is also significant heterogeneity of effects among studies (ie, several studies [1][2][3]6,[13][14][15]18,20,24 did not demonstrate an association between these factors and the risk of PCF formation). On the other hand, while increased risk of PCF was not shown to be associated with concurrent neck dissection and comorbid illness, the heterogeneity of effects among studies was significant.…”
Section: Commentmentioning
confidence: 99%
“…5 Traditionally, clinical studies have documented a 10% to 20% incidence of PCF after TLR. [6][7][8] These studies are mainly based on primary TLR. During the last decade, several studies have demonstrated improvement of outcome and a higher rate of larynx preservation after chemoradiation therapy over radiotherapy alone for advanced laryngeal cancer.…”
mentioning
confidence: 99%